Two distinct catalytic pathways for GH43 xylanolytic enzymes unveiled by X-ray and QM/MM simulations - Mariana A. B. Morais; Joan Coines; Mariane N. Domingues; Renan A. S. Pirolla; Celisa C. C. Tonoli; Camila R. Santos; Jessica B. L. Correa; Fabio C. Gozzo; Carme Rovira; Mario T. Murakami (Nature Communications, 2021)
Family 43 glycoside hydrolases (GH43) are involved in the breakdown of hemicellulose. Functional, structural and computational characterization of a GH43 enzyme, including a snapshot of an active Michaelis complex, reveal the hydrolysis mechanism and suggest two possible reaction pathways.